PENGARUH PEMILIHAN JENIS TUMPUAN TERHADAP PERILAKU STRUKTUR GEDUNG - Baskoro Abdi Praja (Universitas Bina Taruna Gorontalo, 2023)
The use of software is important in the process of planning and structural analysis, specifically the ETABS software. However, the use of software needs to be based on technical concepts and considerations so that technical execution can be carried out in accordance with expectations and targets, for example regarding the selection of the type of support. There are 2 types of supports, namely pin supports and pin supports. These two supports will be the comparison variables with the 4-storey reinforced concrete building modeling system. The analysis was carried out by applying static loads and spectrum response earthquake loads. From this analysis, a comparative study was obtained with a focus on the vibration period of the structure and the magnitude of support reaction values. The bearing reaction in the Z direction on the pin supports is found to be greater than the fixed supports but does not have a moment value so this is very practical for the benefit of substructure design.